Two essays on the brazilian neutral rate: international trends, fiscal determinants - Proença, Leonardo Dias (2022)
The estimates for the Brazilian neutral rate are plenty, but not many works have used them as a dependent variable. We propose two separate essays. In the first, we investigate international trends. We find a long term relationship between the Brazilian neutral rate and its developed economies and Latin American counterparts, separately. Around 25% of the variance of the Brazilian neutral rate can be explained by shocks to other countries, in both versions. In the second, we study the fiscal determinants of neutral rates. Using different specifications and focusing on the expectations of future fiscal variables, we argue that during the domestic crisis of 2014-2016 the fiscal deterioration contributed to an increase of one percentage point in neutral rates.